Denying Darwin. - Orr, H. Allen; Dawkins, Richard (Commentary)
Presents various views on author David Berlinski's criticism of Darwinism. Dependence of Darwinism on random mutations; Role of mathematics in evolutionary biology; Berlinski's alleged failure to understand the role of determinism in evolution.